Characterization of NaxLi0.67+yNi0.33Mn0.67O2 as a positive electrode material for lithium-ion batteries. Issue 46 (24th July 2018) - Chiba, K.; Shikano, M.; Sakaebe, H.
Abstract : The relationship between the charge–discharge properties and crystal structure of Na x Li0.67+ y Ni0.33 Mn0.67 O2 (0.010 ≤ x ≤ 0.013, 0.16 ≤ y ≤ 0.20) has been investigated. Abstract : The relationship between the charge–discharge properties and crystal structure of Na x Li0.67+ y Ni0.33 Mn0.67 O2 (0.010 ≤ x ≤ 0.013, 0.16 ≤ y ≤ 0.20) has been investigated. Li/Na x Li0.67+ y Ni0.33 Mn0.67 O2 cells exhibit gradually sloping initial charge and discharge voltage–capacity curves. The initial charge capacity increased from 171 mA h g −1 for thermally-treated Na0.15 Li0.51 Ni0.33 Mn0.67 O2 to 226 mA h g −1 for Na0.010 Li0.83 Ni0.33 Mn0.67 O2 with an increase in the Li content. The initial maximum discharge capacity was 252 mA h g −1 in the case of Na0.010 Li0.83 Ni0.33 Mn0.67 O2 between 4.8 and 2.0 V at a fixed current density of 15 mA g −1 (0.06C) at 25 °C. The predominance of the spinel phase leads to the high initial discharge capacity of Na0.010 Li0.83 Ni0.33 Mn0.67 O2 . This study shows that chemical lithiation using LiI is effective to improve the electrochemical properties.